MIL-88A@WS2 composite material and its preparation method and application
By using MIL-88A@WS2 composite material and peroxy monosulfate, the multiple problems of traditional Fenton technology in treating phenolic pollutants were solved, and efficient and environmentally friendly phenolic pollutants were achieved.
Patent Information
- Application Number
- CN202510038080.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-10
AI Technical Summary
When dealing with phenolic pollutants, traditional Fenton technology has problems such as narrow pH range, unrecyclable catalysts, iron sludge production, secondary pollution and low H2O2 utilization rate, making it difficult to achieve efficient and environmentally friendly wastewater treatment.
The MIL-88A@WS2 composite material is used as the catalyst for the heterogeneous Fenton reaction system. The WS2, which is mainly 1T phase, is mixed with MIL-88A through hydrothermal reaction to form a composite material with hollow core-shell structure, which is used to work with peroxy monosulfate to degrade phenolic pollutants.
It achieves efficient degradation of phenolic pollutants, expands the scope of pH application, improves catalytic activity and reusability, avoids the generation of iron sludge, and does not require light conditions, and saves energy.
Smart Images

Figure CN119456036B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmentally friendly materials, and in particular relates to a MIL-88A@WS2 composite material and a preparation method and application thereof. Background Art
[0002] Toxic phenolic pollutants are often found in wastewater. Among the many phenolic substances, phenol is a highly toxic compound that is produced in large quantities in wastewater from oil refining and petrochemical enterprises. This substance poses a serious threat to humans and a variety of aquatic organisms. In addition, due to its poor biodegradability, discharge into the environment will cause long-term and serious pollution problems.
[0003] In recent years, the treatment technology of phenol wastewater is still a hot topic in the field of environmental protection. Traditional processes such as physical methods such as adsorption, membrane separation, coagulation and extraction can achieve deep treatment and have good treatment effects, but the treatment capacity is limited and it is not suitable for high-concentration, large-scale wastewater treatment projects, and needs to be combined with other processes; although oxidation and electrolysis in chemical methods are more efficient, their reagent costs and equipment costs are high; biological methods for wastewater treatment are limited by the difficulty of biodegradation of phenol pollutants, not only the treatment cycle is long, but also the mineralization rate of phenol pollutants is low, and some even cause secondary pollution. Therefore, under the current situation, an efficient treatment method is urgently needed.
[0004] The Fenton technology in advanced oxidation technology has the characteristics of high treatment efficiency, relatively low cost and relatively easy industrial application, and has gradually become one of the main methods for deep wastewater treatment. However, the traditional homogeneous Fenton process still has many defects in practical application, mainly: (1) the applicable pH range is narrow, and the optimal operating pH is 3.0; (2) the catalyst cannot be recycled; (3) a large amount of iron sludge is generated, causing secondary pollution; (4) the utilization rate of H2O2 is not high; (5) Fe 2+ The rate of activating H2O2 to produce •OH radicals is very low, and Fe 3+ with Fe 2+ The mutual conversion efficiency is very low. It is urgent to improve the traditional Fenton technology, continuously reduce the adverse effects in the reaction, and promote the wider application of Fenton reaction.
[0005] The heterogeneous Fenton-like reaction system developed to improve the traditional Fenton technology has stronger catalytic ability, wider pH application range, lower metal dissolution, and better reusability, and has become a research hotspot for advanced oxidation technology at home and abroad. At present, the research on heterogeneous Fenton-like reaction systems mainly focuses on the preparation of heterogeneous catalysts and the transformation of reaction systems. The research focus of heterogeneous catalysts is mainly on the preparation of catalysts containing transition metal ions, and the research focus of the transformation of reaction systems is mainly on the transformation of oxidants and changes in reaction conditions, such as the introduction of electricity or light. The above studies have solved the problems existing in the homogeneous Fenton reaction system to varying degrees and have practical research significance.
[0006] Metal-organic framework composites have the advantages of porosity, multifunctionality, diverse structures, and controllable chemical composition, and have attracted widespread attention in the field of heterogeneous catalysts. The environmentally friendly and low-toxic material MIL-88A is composed of Fe 3+ The three-dimensional framework is formed by connecting octahedral trimers with divalent fumarate ions. The presence of coordinated unsaturated iron sites in the trimer Fe3-μ3-O cluster enables it to interact strongly with oxidants, thereby efficiently activating oxidants to produce free radicals.
[0007] Compared with homogeneous reducing agents, heterogeneous metal sulfide co-catalysts such as Cr2S3, Bi2S3, CuS, ZnS, MoS2 or WS2 have attracted the interest of researchers due to their graphene-like layered structure and excellent semiconductor properties. Among the many sulfide co-catalysts, WS2 is the co-catalyst with the strongest reducing ability.
[0008] Currently, a tungsten sulfide-modified iron-based MOF photo-Fenton catalyst has been disclosed. However, the tungsten sulfide-modified iron-based MOF photo-Fenton catalyst prepared by the existing method has the following technical defects: since tungsten sulfide and the iron-based MOF material are simply compounded to form a whole, the obtained tungsten sulfide-modified iron-based MOF photo-Fenton catalyst has few active sites and poor conductivity, which in turn leads to poor catalytic performance. Summary of the invention
[0009] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a MIL-88A@WS2 composite material and a preparation method and application thereof. The present invention mixes WS2 mainly composed of 1T phase with MIL-88A and performs a hydrothermal reaction to obtain a MIL-88A@WS2 composite material with a hollow core-shell structure. The MIL-88A@WS2 composite material obtained by the method of the present invention has a large specific surface area, many active sites, strong conductivity, and can work together with the oxidant peroxymonosulfate to achieve the degradation of phenolic pollutants.
[0010] The present invention is achieved through the following technical solutions:
[0011] The preparation method of the MIL-88A@WS2 composite material comprises the following steps:
[0012] WS2 mainly composed of 1T phase and MIL-88A were mixed in a solvent and then subjected to a hydrothermal reaction. During the hydrothermal reaction, WS2 mainly composed of 1T phase was loaded on MIL-88A and formed Fe 2+ / Fe 3+ and W 4+ / W 6+ In the cyclic channel, there are covalent bonds and ionic bonds between WS2 mainly composed of 1T phase and MIL-88A, and MIL-88A forms a hollow structure to obtain MIL-88A@WS2 composite material.
[0013] Among them, the mass ratio of WS2 mainly composed of 1T phase and MIL-88A is 2:1~8, and this ratio is obtained experimentally.
[0014] The solvent is composed of ethylene glycol and deionized water, and the volume ratio of the two is 5:1. Only by carrying out a hydrothermal reaction in this solvent can MIL-88A form a hollow structure.
[0015] Preferably, the mass ratio of WS2 mainly composed of 1T phase and MIL-88A is 2:1. Experimental results show that among the MIL-88A@WS2 composite materials obtained when the mass ratio of WS2 mainly composed of 1T phase and MIL-88A is 0.2:0.1, 0.2:0.2, 0.2:0.4, 0.2:0.6 or 0.2:0.8, the MIL-88A@WS2 composite material obtained with a mass ratio of 0.2:0.1 has the best performance. This is because too much WS2 wrapped on MIL-88A will result in WS2 not being compounded on MIL-88A, and too little will result in incomplete WS2 wrapping of MIL-88A.
[0016] Preferably, the conditions for the hydrothermal reaction are: heating at 100°C~120°C for 10h~12h; temperature and time outside this range will lead to incomplete reaction, uneven preparation of the MIL-88A@WS2 composite material, or failure to form a hollow MIL-88A.
[0017] Preferably, MIL-88A is prepared according to the following steps: FeCl3•6H2O and fumaric acid are mixed in water, and then heated at 80°C to 100°C for 12h to 14h to obtain MIL-88A.
[0018] Preferably, the molar ratio of the soluble tungsten salt to thioacetamide is 2.5:15-37.5.
[0019] Preferably, WCl6 and thioacetamide are mixed in anhydrous ethanol, and then heated at 180℃~200℃ for 20h~24h to obtain WS2 with 1T phase as the main phase. Different solvents lead to different morphologies of WS2 obtained, and WS2 prepared with ethanol as solvent has stronger reducing ability. The main influencing factors for the preparation of WS2 with 1T phase as the main phase are temperature and the ratio of soluble tungsten salt to thioacetamide. The increase in temperature is conducive to amino intercalation, and the nanoflower structure is more obvious; the ratio of soluble tungsten salt to thioacetamide also affects amino intercalation. The more thioacetamide, the more obvious the amino intercalation; however, after too much amino embedding, the lattice fringe spacing of some crystal planes of WS2 is enlarged, causing it to change from 2H phase to 1T phase, so when there is too much amino intercalation, the prepared phase is 1T phase.
[0020] The present invention also protects the MIL-88A@WS2 composite material obtained by the above preparation method. In the MIL-88A@WS2 composite material, the hollow MIL-88A is used as the core and WS2 is used as the shell, and WS2 is coated on the hollow MIL-88A.
[0021] The present invention also protects the application of the above-mentioned MIL-88A@WS2 composite material in the degradation of phenolic pollutants in a heterogeneous Fenton-like reaction system.
[0022] Preferably, the MIL-88A@WS2 composite material, peroxymonosulfate and phenolic pollutants are mixed to degrade the phenolic pollutants.
[0023] Preferably, the mass ratio of the MIL-88A@WS2 composite material to peroxymonosulfate is 0.07~0.08:0.111~0.1228. Further, the mass ratio of the MIL-88A@WS2 composite material to peroxymonosulfate is 0.08:0.1228.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. In the present invention, WS2 mainly composed of 1T phase is mixed with MIL-88A and subjected to hydrothermal reaction. At this time, WS2 is loaded on MIL-88A, and under the action of the solvent, MIL-88A becomes a hollow structure, thereby obtaining a MIL-88A@WS2 composite material with a hollow MIL-88A as a core and WS2 as a shell.
[0026] In the MIL-88A@WS2 composite material obtained by the method of the present invention, the hollow structure can provide more active sites and can also react with phenolic pollutants; the MIL-88A@WS2 composite material has Fe 2+ / Fe 3+ and W 4+ / W 6+The high-speed circulation channel and the existence of covalent and ionic bonds between WS2 dominated by 1T phase and MIL-88A can better activate the oxidant peroxymonosulfate and produce free radicals and non-free radicals with strong oxidizing properties to oxidize phenolic pollutants; in the MIL-88A@WS2 composite material, the rapid charge transfer between the Fe and W bimetallic active sites enhances the catalytic activity for peroxymonosulfate.
[0027] 2. The present invention catalyzes peroxymonosulfate, thereby overcoming the problem of short lifetime of hydroxyl radicals in the prior art catalyzing hydrogen peroxide; the present invention uses the MIL-88A@WS2 composite material as a catalyst for a heterogeneous Fenton-like reaction system, and compared with traditional catalysts, the pH application range is significantly broadened, and peroxymonosulfate can be efficiently catalyzed in the pH range of 2 to 10 to achieve the degradation of phenolic pollutants; the MIL-88A@WS2 composite material of the present invention overcomes the technical defects of poor stability of the prior art catalysts due to metal precipitation or structural collapse due to the presence of covalent bonds and ionic bonds; the MIL-88A@WS2 composite material of the present invention has good reusability; since Fe ions will not produce iron hydroxide precipitation and form iron mud due to the increase in pH, the MIL-88A@WS2 composite material avoids the problem of iron mud. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Figure 3 is an electron microscope characterization diagram, wherein Figure a is a SEM diagram of WS2 prepared at a mass ratio of WCl6 to thioacetamide of 1:6, Figure b is a SEM diagram of WS2 prepared at a mass ratio of WCl6 to thioacetamide of 1:9, Figure c is a SEM diagram of WS2 prepared at a mass ratio of WCl6 to thioacetamide of 1:12, Figure d is a SEM diagram of WS2 prepared at a mass ratio of WCl6 to thioacetamide of 1:15, Figure e is a SEM diagram of MIL-88A, Figure f is a scanning electron microscope diagram of the MIL-88A@WS2 composite material of Example 1, Figure g is a transmission electron microscope diagram of the MIL-88A@WS2 composite material of Example 1, and Figure h is an enlarged transmission electron microscope diagram of the MIL-88A@WS2 composite material of Example 1; Figure i is a SEAD diffraction diagram of the MIL-88A@WS2 composite material of Example 1.
[0029] Figure 2 The figures are XPS graphs of the MIL-88A@WS2 composite material of Example 1 before and after a heterogeneous Fenton-like reaction; wherein (a) is the overall XPS spectrum before and after the reaction, (b) is the high-resolution XPS graph of C before and after the reaction, (c) is the high-resolution XPS graph of O before and after the reaction, (d) is the high-resolution XPS graph of Fe before and after the reaction, (e) is the high-resolution XPS graph of W before and after the reaction, and (f) is the high-resolution XPS graph of S before and after the reaction.
[0030] Figure 3 The nitrogen adsorption and desorption diagram of the MIL-88A@WS2 composite material of Example 1, WS2 and the MIL-88A of Example 1 is shown in FIG. Figure 3 The small figure in the figure is the pore size distribution diagram of the MIL-88A@WS2 composite material of Example 1, WS2 and MIL-88A of Example 1.
[0031] Figure 4 Electrochemical impedance spectra of the MIL-88A@WS2 composite material of Example 1, WS2 and MIL-88A of Example 1.
[0032] Figure 5 It is a simulated pollutant degradation curve diagram, wherein (a) Figure is a simulated pollutant degradation curve diagram of the MIL-88A@WS2 composite material of Example 1, WS2 / PMS mixed with WS2 and peroxymonosulfate, MIL-88A / PMS mixed with peroxymonosulfate, peroxymonosulfate PMS, and MW-0.1 / PMS mixed with peroxymonosulfate of the MIL-88A@WS2 composite material of Example 1; (b) Figure is a simulated pollutant degradation curve diagram of the MIL-88A@WS2 composite materials of Examples 1 to 5; (c) Figure is a simulated pollutant degradation curve diagram of the MIL-88A@WS2 composite material of Example 1 under different pH conditions.
[0033] Figure 6 These are cyclic stability test diagrams, where (a) is a stability test diagram of the MIL-88A@WS2 composite material of Example 1 after 1-5 cycles; (b) is an XRD diagram of MW-0.1 of Example 1 before and after the cycle.
[0034] Figure 7 Electron paramagnetic resonance images of WS2 and the MIL-88A@WS2 composite material of Example 1. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] Compared with the existing tungsten sulfide modified iron-based MOF photo-Fenton catalyst, the advantages of the present invention are:
[0037] (1) The WS2 obtained by the preparation method of the present invention is mainly 1T phase, which is a tetragonal crystal system with octahedral coordination to form a 1T type crystal structure; while the existing WS2 is 2H phase, which is a trigonal crystal system with trigonal prism and hexagonal crystal system to form a 2H type crystal structure; so the two WS2 are fundamentally different. The conductivity of the 1T phase is 6-7 orders of magnitude higher than that of the 2H phase, and the number of active sites exposed is greater.
[0038] (2) In the present invention, MIL-88A and WS2 mainly composed of 1T phase are prepared separately and then reacted in ethylene glycol to obtain MIL-88A@WS2 with a hollow core-shell structure, so that the specific surface area of the MIL-88A@WS2 composite material is significantly improved and the number of active sites is increased.
[0039] (3) In the prior art, the Fenton reaction is carried out under the conditions of tungsten sulfide modified iron-based MOF photo-Fenton catalyst + light + H2O2, which belongs to the photo-Fenton reaction; the present invention is carried out under a heterogeneous Fenton reaction system, and only uses MIL-88A@WS2 composite material + peroxymonosulfate to achieve effective degradation of phenolic pollutants within 30 minutes, without the need for light conditions, thus saving energy.
[0040] (4) Compared with H2O2 as an oxidant, the present invention uses peroxymonosulfate as an oxidant. Based on the chain reaction initiated by the cleavage of the peroxy bond in the peroxymonosulfate molecule, sulfate radicals with stronger oxidizing ability, longer half-life and higher redox potential are generated compared with hydroxyl radicals, and the target pollutants are degraded with highly active species. In addition, the sulfate radicals generated by peroxymonosulfate have extremely strong oxidizing ability and can quickly kill microorganisms in water. Peroxymonosulfate is denoted as PMS. The redox potential of peroxymonosulfate as an oxidant is 2.5eV~3.1eV, the half-life is 30~40μs, and it is easy to transport, overcoming the defect of inconvenient transportation of H2O2 as an oxidant.
[0041] Based on the current research status of heterogeneous Fenton-like reaction systems, the present invention prepares a MIL-88A@WS2 composite material that is easy to separate and recover in Fenton-like reactions, has a wide pH application range, has a high reuse rate, and is not prone to producing iron sludge, so as to solve the problems existing in the catalysts of the prior art heterogeneous Fenton-like reaction systems and provide technical support and data support for industrial applications.
[0042] The technical solution of the present invention is further studied by using embodiments below, and the specific research methods and results are as follows:
[0043] Before preparing the MIL-88A@WS2 composite material, the present invention screened the mass ratio of WCl6 to thioacetamide to obtain the WS2 with the best performance mainly composed of 1T phase, as shown below:
[0044] Preparation of WS2: Prepared by a one-step hydrothermal method, weigh 0.9914g, 2.5mmol WCl6, 1.1270g, 15mmol thioacetamide, add thioacetamide and WCl6 into a beaker containing 60mL anhydrous ethanol, stir for 30min to mix the two evenly, and then heat at 200℃ for 24h in a 100mL Teflon-lined hydrothermal reactor; after the reactor is naturally cooled to room temperature, the black product produced in the reaction system is collected, washed alternately with deionized water and anhydrous ethanol for 6 times, and finally dried at 70℃ in a vacuum drying oven for 12h to obtain WS2. At this time, the mass ratio of WCl6 to thioacetamide is 1:6, recorded as W 1:6 .
[0045] Preparation of WS2: Prepared by a one-step hydrothermal method, weigh 0.9914g, 2.5mmol WCl6, 1.6904g, 22.5mmol thioacetamide, add thioacetamide and WCl6 into a beaker containing 60mL anhydrous ethanol, stir for 30min to mix the two evenly, and then heat at 200℃ for 24h in a 100mL Teflon-lined hydrothermal reactor; after the reactor is naturally cooled to room temperature, the black product produced in the reaction system is collected, washed alternately with deionized water and anhydrous ethanol for 6 times, and finally dried at 70℃ in a vacuum drying oven for 12h to obtain WS2. At this time, the mass ratio of WCl6 to thioacetamide is 1:9, recorded as W 1:9 .
[0046] Preparation of WS2: Prepared by a one-step hydrothermal method, weigh 0.9914g, 2.5mmol WCl6, 2.2539g, 30mmol thioacetamide, add thioacetamide and WCl6 into a beaker containing 60mL anhydrous ethanol, stir for 30min to mix the two evenly, and then heat at 200℃ for 24h in a 100mL Teflon-lined hydrothermal reactor; after the reactor is naturally cooled to room temperature, the black product produced in the reaction system is collected, washed alternately with deionized water and anhydrous ethanol for 6 times, and finally dried at 70℃ in a vacuum drying oven for 12h to obtain WS2. At this time, the mass ratio of WCl6 to thioacetamide is 1:12, recorded as W 1:12 .
[0047] Preparation of WS2: Prepared by a one-step hydrothermal method, weigh 0.9914g, 2.5mmol WCl6, 2.8175g, 37.5mmol thioacetamide, add thioacetamide and WCl6 into a beaker containing 60mL anhydrous ethanol, stir for 30min to mix the two evenly, and then heat at 200℃ for 24h in a 100mL Teflon-lined hydrothermal reactor; after the reactor is naturally cooled to room temperature, the black product produced in the reaction system is collected, washed alternately with deionized water and anhydrous ethanol for 6 times, and finally dried at 70℃ in a vacuum drying oven for 12h to obtain WS2. At this time, the mass ratio of WCl6 to thioacetamide is 1:15, recorded as W 1:15 .
[0048] To W 1:6 , W 1:9 , W 1:12 and W 1:15 To characterize the morphology, Figure 1 The results in Figure a show that when the mass ratio of WCl6 to thioacetamide is 1:6, the surface is almost a smooth sphere, and the surface of WS2 lacks amino intercalation; Figure 1 The results in Figure b show that when the mass ratio of WCl6 to thioacetamide is 1:9, some nanoflower-like structures appear on the surface, but the surface of WS2 also lacks amino intercalation; Figure 1 The results in Figure c show that when the mass ratio of WCl6 to thioacetamide is 1:12, a dense nanoflower-like structure appears on the surface, and the amino intercalation on the surface of WS2 is relatively abundant; Figure 1 The results in Figure d show that when the mass ratio of WCl6 to thioacetamide is 1:15, the surface is still a dense nanoflower-like structure, and the amino intercalation on the WS2 surface reaches saturation; in contrast, when the mass ratio of WCl6 to thioacetamide is 1:12, the obtained WS2 is the best.
[0049] In the following embodiments, W is used 1:12 The raw materials are compounded with MIL-88A as shown below:
[0050] Example 1
[0051] The preparation method of the MIL-88A@WS2 composite material comprises the following steps:
[0052] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and then placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 100°C forced air drying oven for 12 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0053] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0054] Preparation of S2 and MIL-88A@WS2: 0.2 g of W 1:12 It was mixed with 0.1 g of MIL-88A in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, it was placed in a 50 mL Teflon-lined hydrothermal reactor, heated at 120 °C for 12 h, washed and dried to obtain a MIL-88A@WS2 composite material, recorded as MW-0.1.
[0055] Example 2
[0056] The preparation method of the MIL-88A@WS2 composite material is the same as the preparation steps of Example 1, except that in step S2, the mass of MIL-88A is replaced from 0.1 g to 0.2 g, and includes the following steps:
[0057] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and then placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 100°C forced air drying oven for 12 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0058] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0059] Preparation of S2 and MIL-88A@WS2: 0.2 g of W 1:12It was mixed with 0.2 g of MIL-88A in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, it was placed in a 50 mL Teflon-lined hydrothermal reactor, heated at 120 °C for 12 h, washed and dried to obtain a MIL-88A@WS2 composite material, recorded as MW-0.2.
[0060] Example 3
[0061] The preparation method of the MIL-88A@WS2 composite material is the same as the preparation steps of Example 1, except that in step S2, the mass of MIL-88A is replaced from 0.1 g to 0.4 g, and includes the following steps:
[0062] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and then placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 100°C forced air drying oven for 12 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0063] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0064] Preparation of S2 and MIL-88A@WS2: 0.2 g of W 1:12 It was mixed with 0.4 g of MIL-88A in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, it was placed in a 50 mL Teflon-lined hydrothermal reactor, heated at 120 °C for 12 h, washed and dried to obtain a MIL-88A@WS2 composite material, recorded as MW-0.4.
[0065] Example 4
[0066] The preparation method of the MIL-88A@WS2 composite material is the same as the preparation steps of Example 1, except that in step S2, the mass of MIL-88A is replaced from 0.1 g to 0.6 g, and includes the following steps:
[0067] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and then placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 100°C forced air drying oven for 12 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0068] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0069] S2, preparation of MIL-88A@WS2: 0.2 g of WS2 and 0.6 g of MIL-88A were mixed in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, the mixture was placed in a 50 mL Teflon-lined hydrothermal reactor and heated at 120 °C for 12 h. The mixture was washed and dried to obtain a MIL-88A@WS2 composite material, recorded as MW-0.6.
[0070] Example 5
[0071] The preparation method of the MIL-88A@WS2 composite material is the same as the preparation steps of Example 1, except that in step S2, the mass of MIL-88A is replaced from 0.1 g to 0.8 g, and includes the following steps:
[0072] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and then placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 100°C forced air drying oven for 12 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0073] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0074] S2, preparation of MIL-88A@WS2: 0.2 g of WS2 and 0.8 g of MIL-88A were mixed in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, the mixture was placed in a 50 mL Teflon-lined hydrothermal reactor and heated at 120 °C for 12 h. The mixture was washed and dried to obtain a MIL-88A@WS2 composite material, recorded as MW-0.8.
[0075] Example 6
[0076] The preparation method of the MIL-88A@WS2 composite material comprises the following steps:
[0077] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 80°C forced air drying oven for 14 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0078] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0079] Preparation of S2 and MIL-88A@WS2: 0.2 g of W 1:12 It was mixed with 0.1 g of MIL-88A in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, it was placed in a 50 mL Teflon-lined hydrothermal reactor, heated at 100 °C for 11 h, washed and dried to obtain the MIL-88A@WS2 composite material.
[0080] Example 7
[0081] The preparation method of the MIL-88A@WS2 composite material comprises the following steps:
[0082] S1. Preparation of MIL-88A: Prepared by a one-step hydrothermal method, 10 mmol of FeCl3•6H2O and 10 mmol of fumaric acid were placed in a beaker filled with 50 mL of deionized water, stirred for 15 min, and placed in a 150 mL Teflon-lined stainless steel high-pressure reactor, and heated in a 90°C forced air drying oven for 13 h to react; after the reaction was completed, it was naturally cooled to room temperature, and the orange-brown product was separated by centrifugation at a speed of 8000 r / min and a separation time of 8 min. After being fully and alternately washed with deionized water and anhydrous ethanol, it was vacuum dried at 333 K for 12 h to obtain MIL-88A.
[0083] Among them, the mass of FeCl3•6H2O is 2.703g, and the mass of fumaric acid is 1.1607g.
[0084] Preparation of S2 and MIL-88A@WS2: 0.2 g of W 1:12 It was mixed with 0.1 g of MIL-88A in a mixed solvent of 25 mL of ethylene glycol and 5 mL of deionized water. After ultrasonic treatment for 30 min, it was placed in a 50 mL Teflon-lined hydrothermal reactor, heated at 110 °C for 10 h, washed and dried to obtain the MIL-88A@WS2 composite material.
[0085] In the present invention, the heterogeneous Fenton-like catalyst MIL-88A@WS2 composite materials are prepared in Examples 1 to 7. The MIL-88A@WS2 composite materials of Examples 1 to 5 are used as examples for research. The specific research methods and results are as follows:
[0086] Figure 1 The results in Figure e show that MIL-88A has a spindle-rod structure and MIL-88A was successfully prepared; Figure 1 The results in Figure f show that WS2 is loaded on MIL-88A in a nanoflower layered structure; Figure 1 The g-diagram results in the figure show that MW-0.1 exists in the form of a hollow; Figure 1 The h-diagram results in the figure show that there are 1T phase and 2H phase WS2 in MW-0.1; Figure 1 The results of Figure i show that lattice diffraction rings of WS2 appear.
[0087] The MW-0.1 of Example 1 was used to carry out a heterogeneous Fenton-like reaction, and the reaction process was as follows: MW-0.1 was added to a glass beaker containing 200 mL, 20 mg / L phenol solution, and after reacting in the dark for 30 min to reach adsorption equilibrium, peroxymonosulfate was added to the above solution, and the mass ratio of MW-0.1 to peroxymonosulfate was 0.06:0.1228, initiating a heterogeneous Fenton-like reaction. 4 mL of the suspension reacted for 60 min was extracted, 0.2 mL of methanol was added as a quencher to terminate the reaction, and after filtering with a 0.22 μm filter membrane, 2 mL of supernatant was extracted for determination. Phenol was determined by tetraamine antipyrine spectrophotometry, and was determined by a 722G Chinese visible spectrophotometer at a wavelength of 510 nm.
[0088] Figure 2 The results in Figure (a) show that C, O, Fe, W, and S exist on the surface of MW-0.1 before and after the reaction, indicating that MIL-88A and WS2 are successfully composited; Figure 2 The results in Figure (b) show that there are CC bonds, CO bonds and carboxyl groups in MW-0.1, and these groups are derived from the benzoic acid ring in MIL-88A; Figure 2 The results in Figure (c) show that the three obvious peaks belong to WO, Fe-O and -COOH, respectively, indicating that WS2 and MIL-88A exist in MW-0.1; Figure 2 The results in Figure (d) show that before and after the reaction, Fe 2+ and Fe 3+ The relative content of has changed, and Fe ions have participated in the reaction; Figure 2 The results in Figure (e) show that before and after the reaction, W 4+ and W 6+ The relative content of has changed, and W ions have participated in the reaction; Figure 2 The results in Figure (f) show that S 2- The relative content of changed, S ions participated in the reaction, and sulfur vacancies appeared after the reaction.
[0089] Figure 3 The results showed that the heterostructure of MW-0.1 effectively increased the surface area of MIL-88A and provided more active sites.
[0090] Figure 4 The results show that compared with MW-0.1, MIL-88A and WS2 have better charge transfer due to the better conductivity of MW-0.1, thus improving the catalytic performance.
[0091] WS2 is mixed with peroxymonosulfate to obtain WS2 / PMS, wherein the mass ratio of WS2 to peroxymonosulfate is 0.06:0.1228.
[0092] MIL-88A and peroxymonosulfate are mixed to obtain MIL-88A / PMS; wherein the mass ratio of MIL-88A to peroxymonosulfate is 0.06:0.1228.
[0093] MW-0.1 and peroxymonosulfate are mixed to obtain MW-0.1 / PMS; wherein the mass ratio of MW-0.1 to peroxymonosulfate is 0.06:0.1228.
[0094] Figure 5 The test method of Figure (a) is as follows: take 5 beakers, add 0.4g / L of MIL-88A, MW-0.1, WS2, and MW-0.1 to the first 4 beakers respectively, then add phenol solution to the first 4 beakers respectively; add phenol solution to the 5th beaker and stir. Figure 5 -30min~0min is the adsorption time, that is, MIL-88A, WS2, MW-0.1, and MW-0.1 are first added to adsorb phenol, and the adsorption time is 30min. After the adsorption, 0.1228g of PMS is added to MIL-88A, WS2, one of the beakers containing MW-0.1, and the beaker with only phenol solution, respectively, to obtain WS2 / PMS, MIL-88A / PMS, MW-0.1 / PMS, and PMS samples. The phenol solution is 20mg / L, the initial pH is 7.0, the total volume is 200mL, and they are stirred and mixed at room temperature. Figure 5 The results in Figure (a) show that compared with MW-0.1, PMS, MIL-88A / PMS, and WS2 / PMS, MW-0.1 / PMS has a significant improvement on the degradation of phenol, indicating that MW-0.1 has a synergistic effect on the activation of PMS.
[0095] Figure 5 The test method of Figure (b) is: 0.4 g / L MW-0.1 of Example 1, MW-0.2 of Example 2, MW-0.4 of Example 3, MW-0.6 of Example 4 and MW-0.8 of Example 5 are mixed with phenol solution, -30 min ~ 0 min is the adsorption time, 1 mmol / L of PMS solution is added after the adsorption, the amount of phenol solution is 20 mg / L, the initial pH is 7.0, the total volume is 200 mL, and the mixture is stirred at room temperature. Figure 5 The results in Figure (b) show that the catalytic effect is best when the mass ratio of MIL-88A to WS2 is 2:1, that is, MW-0.1 has the best catalytic effect.
[0096] Figure 5The test method in Figure (c) is as follows: 0.4 g / L of MW-0.1 of Example 1 is placed in phenol solutions with pH values of 3.0, 5.0, 7.0, 9.0, and 11.0, respectively, and the adsorption time is from -30 min to 0 min. After the adsorption, 1 mmol / L of PMS solution is added, respectively. The amount of phenol solution is 20 mg / L, the initial pH value is 7.0, the total volume is 200 mL, and the mixture is stirred and mixed at room temperature. Figure 5 The results in Figure (c) show that MW-0.1 has a good degradation effect on phenol when the pH is between 3 and 9.
[0097] The MW-0.1 of Example 1 was used to carry out a cyclic experiment of phenol degradation. The cyclic method was as follows: 0.4 g / L of the MW-0.1 of Example 1 was placed in a 20 mg / L phenol solution with a pH of 7.0, and adsorbed for 30 min. After the adsorption, 0.1228 g of a PMS solution was added to a total volume of 200 mL. The mixture was stirred and mixed at room temperature, and degraded for 1 h. After the degradation was completed, the MW-0.1 was washed alternately with deionized water and anhydrous ethanol three times, then placed in a vacuum drying oven for drying, and then the MW-0.1 was reused. Figure 6 The results in Figure (a) show that after 5 cycles, the removal rate of phenol can still be maintained at a high level, and MW-0.1 has good stability; Figure 5 Figure (b) shows that the position and intensity of the characteristic peaks indicate that the basic structure remains unchanged, and MW-0.1 can maintain a stable structure and has great potential for practical applications.
[0098] Figure 7 The results show that there are sulfur vacancies in the MIL-88A@WS2 composite material of Example 1. The advantages of sulfur vacancies are: (1) increasing the electron density near the metal site, accelerating electron transfer, and enhancing the electron transfer ability of the MIL-88A@WS2 composite material; (2) sulfur vacancies can expose more metal sites to enhance the activation of PMS.
[0099] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A method for preparing a MIL-88A@WS2 composite material, characterized in that: The steps include: The 1T phase WS2 and MIL-88A were mixed in a solvent and then subjected to a hydrothermal reaction. During the hydrothermal reaction, the 1T phase WS2 was loaded on MIL-88A and formed Fe 2+ / Fe 3+ and W 4+ / W 6+ In the cyclic channel, there are covalent bonds and ionic bonds between 1T phase WS2 and MIL-88A, and MIL-88A forms a hollow structure to obtain MIL-88A@WS2 composite material; Among them, the mass ratio of WS2 to MIL-88A in the 1T phase is 2:1 to 8; The solvent consists of ethylene glycol and deionized water, with a volume ratio of 5:1; The conditions of the hydrothermal reaction are: heating at 100°C to 120°C for 10h to 12h.
2. The method for preparing the MIL-88A@WS2 composite material according to claim 1, characterized in that: The mass ratio of WS2 to MIL-88A in the 1T phase is 2:
1.
3. The method for preparing the MIL-88A@WS2 composite material according to claim 1, characterized in that: MIL-88A was prepared as follows: FeCl3·6H2O and fumaric acid are mixed together in water, and then heated at 80°C to 100°C for 12h to 14h to obtain MIL-88A.
4. The method for preparing the MIL-88A@WS2 composite material according to claim 1, characterized in that: Mix WCl6 and thioacetamide in anhydrous ethanol and then heat at 180℃~200℃ for 20h~24h to obtain 1T phase WS2.
5. A MIL-88A@WS2 composite material obtained by the preparation method according to any one of claims 1 to 4.
6. The MIL-88A@WS2 composite material according to claim 5, characterized in that: In the MIL-88A@WS2 composite material, the hollow MIL-88A is used as the core and WS2 is used as the shell, and WS2 is coated on the hollow MIL-88A.
7. Use of the MIL-88A@WS2 composite material according to claim 5 in preparing a catalyst for degradation of phenolic pollutants in a heterogeneous Fenton-like reaction system.
8. The use according to claim 7, characterized in that: The application method is: mixing the MIL-88A@WS2 composite material, peroxymonosulfate and phenolic pollutants to degrade the phenolic pollutants.
9. The use according to claim 8, characterized in that: The mass ratio of MIL-88A@WS2 to peroxymonosulfate is 0.07~0.08:0.111~0.1228.